Analisis Strategi Pemasaran Syariah pada UMKM - Gita Diana Putri; Husna, Trina Akhsanul; Lilis Renfiana (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
This study aims to describe the analysis of sharia marketing strategies on increasing market share of Kedai Rahil products in Tanjung Kesuma, Purbolinggo District, East Lampung Regency, The method we used in this research is qualitative research methods. Researchers collected data using interview, observation and documentation methods. The study concluded that the analysis of sharia marketing strategies to increase the market share of Kedai Rahil products has been carried out in a sharia manner even though it has not been fully implemented. The marketing strategy carried out uses a marketing mix (marketing mix 4p) which consists of a product strategy, place strategy, promotion strategy, price strategy. With the use of the marketing mix strategy, it can have an impact on increasing market share, the most influential indicators in increasing market share are target market and market position.